Hubungan Persepsi Siswa terhadap Punishment yang Diberikan Guru dan Kecerdasan Emosi dengan Kedisiplinan - Janus Janus (University of Merdeka Malang, 2014)
This study aimed to determine the relationship of students' perceptions of punishment given to teachers and emotional intelligence with discipline. The subjects of this study were junior high school students of Kristen Petra 3 Surabaya eight grade, totaling 127 students. Data collection tools used in this study was scale of students' perception of punishment provided by the teacher, scale of emotional intelligence, and scale of discipline. Based on anareg, obtained anareg correlation coefficient F = 1.085, p = 0.341 (p 0.05). This means that together there is no relationship between students' perceptions of punishment given to teachers and emotional intelligence discipline. Independent variable partial test students' perception of the teacher's punishment resulted in p = 0.155 (p 0.05), this shows the independent variable students' perceptions of teachers' punishment given nothing to do with discipline. Partial test of emotional intelligence independent variable produces a p-value = 0.584 (at p 0.05), the independent variables of emotional intelligence showed no relationship with the discipline.